The Effectiveness of Online Learning Through Google Classroom to Improve the Learning Achievement - Sihombing, Lisbet Novianti; Ambarita, Prini Desima Evawani (Universitas Pendidikan Ganesha, 2022)
During the COVID-19 pandemic, popular applications used by lecturers were applications provided by the campus as well as third-party applications such as Whatsapp, Google Classroom, or Webex. The use of the Google Classroom application has several weaknesses, among others, it can only be accessed by a Google account and there is no notification that the material submitted has been read in full by students so that the effectiveness of Google Classroom is still in doubt. This study aims to analyze the effectiveness of online learning through Google Classroom to improve achievement. learning entrepreneurship for fifth grade elementary school students. This type of research is quantitative research with quantitative descriptive data analysis. The population of this research is 70 students of public elementary school. The data collection technique used is a questionnaire. The hypothesis testing technique uses simple linear analysis, regression linearity and the coefficient of determination. The results showed that online learning through google classroom was effective in improving the entrepreneurship learning achievement of fifth grade elementary school students. This means that it is known that 60% of online learning through google classroom is effective for improving entrepreneurial learning achievement, while the remaining 40% of online learning through google classroom is not effective from other factors not examined in this study.